Surgery results in low relapse and progression rates in extramedullary plasmacytoma of the head and neck: A case cohort and review of the literature - Matevz Skerget; Tadej Dovsak; Gregor Kos; Samo Zver (Hematology Reports, 2020)
Extramedullary plasmacytoma of the head and neck is a rare indolent neoplasm. Radiotherapy is often the preferred treatment option with excellent local control and survival. The risk of local recurrence or transformation to multiple myeloma is 10- 30%. In our case-cohort, thorough, sensitive initial evaluation for disseminated clonal disease and the incorporation of surgery led to excellent results with no recurrences or systemic progression.